2001
DOI: 10.1093/carcin/22.7.999
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of N-acetylcysteine in the prevention of DNA damage and cancer, with special reference to smoking-related end-points

Abstract: Although smoking cessation is the primary goal for the control of cancer and other smoking-related diseases, chemoprevention provides a complementary approach applicable to high risk individuals such as current smokers and ex-smokers. The thiol N-acetylcysteine (NAC) works per se in the extracellular environment, and is a precursor of intracellular cysteine and glutathione (GSH). Almost 40 years of experience in the prophylaxis and therapy of a variety of clinical conditions, mostly involving GSH depletion and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
235
1
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 318 publications
(253 citation statements)
references
References 138 publications
10
235
1
3
Order By: Relevance
“…19,20 The in vitro differentiating action of NAC reported for the first time in the present work is not related to its radical scavenging properties. Indeed, neither antiproliferative effect nor differentiation were induced by the paradigmatic scavenger Trolox C, supplemented to the cell growth medium at concentrations ranging from 0.1 to 0.5 mM.…”
Section: Discussionmentioning
confidence: 55%
“…19,20 The in vitro differentiating action of NAC reported for the first time in the present work is not related to its radical scavenging properties. Indeed, neither antiproliferative effect nor differentiation were induced by the paradigmatic scavenger Trolox C, supplemented to the cell growth medium at concentrations ranging from 0.1 to 0.5 mM.…”
Section: Discussionmentioning
confidence: 55%
“…Furthermore, L-cysteine also has the ability to reduce lipid peroxidation that produces free radicals, and thus protect spermatozoa from ROS [2,4,5]. Besides being active as a glutathione precursor, L-cysteine can also account for a protective effect in the extracellular milieu, primarily due to its nucleophilic and antioxidant properties [30]. …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, experimental studies in vitro and in animal models as well as Phase II clinical trials have shown the ability of NAC to prevent genotoxicity and cancer through a broad variety of mechanisms. 15 NAC has been investigated previously for the ability to prevent tumors at various sites 15,16 but its effect was never assayed in esophageal carcinogenesis. …”
mentioning
confidence: 99%
“…31 Although no epidemiological data are available, DEN should be regarded for practical purposes as if it were carcinogenic to humans, due to its documented carcinogenicity in all animal species tested after administration by various routes. 31 NAC, one of the most promising cancer chemopreventive agents, 15,16 failed to modulate the yield of liver tumors produced by the DEN ϩ DEDTC combination. NAC had been shown previously to be without effects on DEN-induced liver foci and hepatocellular adenomas in C3H mice, 32 whereas it was successful to decrease the number of ␥-GT-positive foci in 2-acetylaminofluorene-treated Sprague-Dawley rats.…”
mentioning
confidence: 99%
See 1 more Smart Citation